2021
DOI: 10.3389/fmed.2021.698495
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgA Antibodies Specific to M. leprae Antigens as Biomarkers for Leprosy Detection and Household Contact Tracking

Abstract: Leprosy remains endemic in several developing countries, such as India and Brazil, in part due to delayed diagnosis that facilitates ongoing transmission. Although immunoglobulins against several Mycobacterium leprae antigens have been indicated for the early diagnosis, and IgA participates in the early stages of leprosy and in subclinical infection, relatively little research has examined anti-M. leprae IgA responses. Here, we investigated serum IgA reactivity against NDO-HSA, LID-1 and NDO-LID, in paucibacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…Serological testing for IgA is presented as an additional tool for the diagnosis and classification of HD, with potential utility for exposure monitoring of household contacts. In agreement with our data, Silva et al ( 19 ) reported greater IgA reactivity against the conjugated antigen formed by natural octyl disaccharide linked to human serum albumin (NDO-HSA) among household contacts of PB and MB patients than among non-endemic controls. Accordingly, α-Mce1A IgA showed satisfactory accuracy (AUC 0.90) with 77.5% sensitivity and 89.0% specificity and revealed greater seropositivity of the immunoglobulins tested in patients, with 77.5% for new cases and 65.7% for contacts.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Serological testing for IgA is presented as an additional tool for the diagnosis and classification of HD, with potential utility for exposure monitoring of household contacts. In agreement with our data, Silva et al ( 19 ) reported greater IgA reactivity against the conjugated antigen formed by natural octyl disaccharide linked to human serum albumin (NDO-HSA) among household contacts of PB and MB patients than among non-endemic controls. Accordingly, α-Mce1A IgA showed satisfactory accuracy (AUC 0.90) with 77.5% sensitivity and 89.0% specificity and revealed greater seropositivity of the immunoglobulins tested in patients, with 77.5% for new cases and 65.7% for contacts.…”
Section: Discussionsupporting
confidence: 93%
“…IgA is an antibody associated with the mucosal response, the main gateway of the bacillus in the establishment of infection, participating in the early stages of HD and in subclinical infection ( 19 – 21 ). The importance of IgA for host mucosal immunity is well established and, although its role in the systemic circulation has not been fully elucidated ( 22 ), its usefulness as an immunological marker in laboratory tests has been confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the screening of different classes of immunoglobulins increases the possibility of diagnosis, with anti-Mce1A IgA being a potential biomarker in the screening of contact with M. leprae . In line with the findings of our study, Silva et al ( 23 ) reports that IgA antibodies play a role in protecting against mycobacteria in the nasal mucosa and a biomarker of contact with the bacillus ( 23 ). As also, the search for an ideal serology is also associated with a satisfactory marker of disease activity.…”
Section: Discussionsupporting
confidence: 93%
“…Even in the absence of symptoms, M. leprae is replicating and invading the host tissues ( 5 ), and biomarkers for the infection as anti-phenolic glycolipid-I (PGL-I) IgM antibodies have been recommended to detect a risk of infection in asymptomatic patients, especially household contacts. Some studies have also suggested a relation between infection in these patients and other biomarkers such as IL-6 and nutritional status ( 6 ), serum levels of IgA antibodies against NDO-HSA ( 7 ), CCL2 chemokine associated with IFN-γ ( 8 ), and IgM profile against NDO-HSA, LID-1, and NDOLID antigens, and monocytes and CD4+ lymphocyte frequency ( 9 ), beyond arginase activity ( 10 ) as a protective marker against this infection.…”
Section: Introductionmentioning
confidence: 99%